Antioxidant Activity of Black Tea and Oolong Tea Extracts as Natural Preservatives in Homemade Cookies - Faroerzy, Nik Nurul Izzah Binti; Razali, Nor Faizah Binti (Progress in Engineering Application and Technology, 2026)
Preservation using natural antioxidants in food has been receiving growing interest because of the safety of synthetic food preservatives. The aim of the study was to determine the possibility of Camellia sinensis, from black tea and oolong tea extract being used as natural antioxidants and substitute preservatives in homemade cookies and to compare the performance of these extracts with a synthetic antioxidant, butylated hydroxyanisole (BHA). Black tea and oolong tea were used to purify antioxidants through the Soxhlet method with isopropanol as a solvent. These extracts were then analysed using various methods, which included the DPPH assay, total phenolic content (TPC), peroxide value (PV), and the antioxidant activity (AOA). The DPPH test showed that the free radical scavenging activity was the highest in BHA (93.01 %), then black tea extract (50.42 %), and oolong tea extract (6.05 %). TPC analysis revealed that black tea extract contained more phenolic compounds as compared to the oolong tea extract, hence a positive relationship between phenolic content and the antioxidant capacities. Both tea extracts were found to be effective when used in homemade cookies in reducing lipid oxidation in 14 days of storage, with the control sample experiencing the most PV increase. The results of the AOA have shown that black tea and oolong tea extracts had a value of 48.05 % and 48.90 %, respectively, which was higher than BHA (21.59 %). These results indicate that even though BHA has a good in vitro antioxidant activity, the tea extracts are more effective in antioxidant protection in actual food systems. Overall, oolong tea extract and black tea extract have good perspectives of effective and safe natural food preservatives.